HUBUNGAN AUDIT OPERASIONAL DAN PENGELOLAAN PERSEDIAAN BARANG DAGANG TERHADAP PENINGKATAN LABA PADA CV ANEKA SPORTS INDONESIA (Studi Kasus Pada Pada CV Aneka Sports Indonesia Tahun 2022) - Muhammad Sopiyana (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to determine the relationship between operational audit and merchandise inventory management simultaneously on increasing profits at CV Aneka Sports Indonesia. To determine the relationship of operational audit partially to the increase in profit at CV Aneka Sports Indonesia. To find out the relationship between the management of merchandise inventory at CV Aneka Sports Indonesia. This research is a quantitative research with the subject of this research is KCP BRI Syariah in South Tangerang, with a sample collection technique, namely Non Probability Sampling with a convention sampling technique, with the number of samples being 32 respondents, the data collection method is carried out by observation, interviews, and data analysis is carried out using descriptive analysis using SPSS. 1) This study proves that the audit Operations have a significant effect on the increase in profit. Based on research, the existence of an Operational Audit can make an increase in profits better, and profits will continue to increase if the activities carried out are assessed and evaluated by the Operational Audit. 2) This study proves that inventory management has a significant effect on increasing profits. So based on research, if inventory management in a company goes well in accordance with the rules in the company, it will be able to increase sales at various Indonesian sports cv companies. 3) This study proves that the Operational Audit and Inventory Management on Increasing Profit at CV Aneka Sport Indonesia have a simultaneous effect and based on research that all variables in this study can increase Profit Increase.